To the division into periods of historical and ukrainoznavchikh researches of social and political processes on zakhidnoukrainskikh earths of end of 1930-kh–1950-kh years - Сорока Ю. (Київський національний університет імені Тараса Шевченка, 2011)
The article deals with the main historiographical Ukrainian Studies' stages of research investigation of the social-political processes in the Western Ukraine Lands in 1939-1959.

В статті розкриваються основні історіографічні та українознавчі етапи дослідження суспільно-політичних процесів на західноукраїнських землях у 1940-х–1950-х рр.
До періодизації історичних та українознавчих досліджень суспільно-політичних процесів на західноукраїнських землях кінця 1930-х–1950-х років